Influence of the Curvature of the Multipoint Die for Flexible Multipoint Stretch Bending on the Quality of Aluminum Profile. (31st January 2020) - Li, Yi; Li, Rui; Liang, Ce; Liang, Jicai; Teng, Fei
Abstract : The finite element numerical simulation method was used to study the stretch-bending process of asymmetric L-section aluminum alloy profiles. The geometrical parameters of the multipoint dies (MPDs) are studied to influence the shape accuracy and springback of the L-section profile after bending. The results show that the profile curvature of the MPD after the profile is bent has a great influence on the stress-strain distribution, springback value, and shape accuracy. In order to obtain uniform stress-strain of the profile and reduce the springback and shape error, the MPD is optimized by numerical simulation analysis, which has a certain reference value of providing a theoretical basis for the rational design of the flexible stretch-bending.